ETHNOPHARMACOLOGICAL STUDY OF SOME PLANTS FROM CIPICUNG VILLAGE, GARUT DISTRICT, WEST JAVA PROVINCE - Meidinata, Dita; Nur Amalia (Akademi Farmasi Yarsi Pontianak, 2025)
Judging from the condition of the natural resources of Cipicung Village, Garut Regency has advantages in the field of agriculture, which is a basic need. So that the basis of research is what medicinal plants are used by the people of Cipicung Village, Garut Regency. The purpose of the study was to document and prove scientifically the medicinal plants with determination used by the people of Cipicung Village, Garut Regency. Research methods with area studies and scientific studies. From the results of ethnopharmacology obtained sidaguri sida plants are useful for gout and malgia, and sendokan/ki leaves are useful for hypertension and diabetes. so that traditional medical knowledge becomes recorded and can be preserved.